Dewan Editor JAT Vol. 7, No. 4, Oktober 2018 - JAT, Pengelola (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.4, Oktober 2018, 2018)
Dewan Editor JAT Vol. 7, No. 4, Oktober 2018